Hematological parameters of rheumatoid arthritis patients undergoing total hip replacement - Anton S. Ershov (Russian Ilizarov Scientific Center for Restorative Traumatology and Orthopaedics, 2021)
Abstract. Background Patients with rheumatoid arthritis (RA) and baseline anemia may have an increased risk of complications after total hip replacement (THR). Inflammation in RA is the main factor manifesting anaemia, neutropenia, thrombocytosis and eosinophilia. The changes in blood components are important for the outcomes of major orthopaedic surgery. The purpose was to identify hematological parameters in RA patients undergoing THR and assess the effect on intraoperative blood loss. Material and methods Outcomes of 44 THR patients treated for grade III degenerative coxarthrosis (n = 21, OA group) and RA coxarthrosis (n = 23, RA group) in Ekaterinburg regional hospital № 1 between 2018 and 2019 were reviewed. The patients' age ranged from 41 to 70 years. Clinical, radiological, laboratory examinations, computed tomography and statistical analysis were used for the study. Cell counting was produced with the Sysmex XT-4000i automated hematology system. Statistical analysis was performed using the tools of Statistica software. Nonparametric Mann-Whitney test was used to compare cell counts between the groups. The Spearman Rank correlation was used to analyse the correlation between the the cell counts in the groups. For calculations, a significance level of р < 0.05 was adopted. Results There were no significant differences in the preoperative white blood cell (WBC), neutrophil, lymphocyte, monocyte, eosinophil counts between RA and OA groups. The RA group showed an evident decrease in red blood cell (RBC) count and haemoglobin level as compared to OA group. The RA group demonstrated the higher platelet count with mean platelet volume (MPV) being significantly lower than that in the OA group. WBC count, neutrophils, in particular, was shown to increase with lymphocyte, RBC, platelet count and hemoglobin, plateletcrit levels decreased at 24 hours postoperatively. There were no significant differences in WBC and RBC counts in the groups postoperatively. The differences in the MPV were leveled up in the groups with the platelet count being higher in the RA group as compared to the OA group. Conclusions Hematological parameters of RA patients who had undergone specific preoperative preparation were not shown to be associated with greater blood loss during hip replacement surgery. The leukocyte count leveled up in the preoperative and early postoperative periods can be indicative of the absence of a significant effect of RA on the postoperative inflammation.